Different Pharmacokinetics of Tramadol, O-Demethyltramadol and N-Demethyltramadol in Postoperative Surgical Patients From Those Observed in Medical Patients - Neskovic, Nenad; Mandic, Dario; Marczi, Saska; Skiljic, Sonja; Kristek, Gordana; Vinković, Hrvoje; Mraovic, Boris; Debeljak, Zeljko; Kvolik, Slavica (Frontiers in Pharmacology, 2021)
Background: Most studies examining tramadol metabolism have been carried out in non-surgical patients and with oral tramadol. The aim of this study was 1) to measure concentrations of tramadol, O-demethyltramadol (ODT), and N-demethyltramadol (NDT) in the surgical patients admitted to the intensive care unit (ICU) within the first 24 postoperative hours after intravenous application of tramadol, and 2) to examine the effect of systemic inflammation on tramadol metabolism and postoperative pain. Methods: A prospective observational study was carried out in the surgical ICU in the tertiary hospital. In the group of 47 subsequent patients undergoing major abdominal surgery, pre-operative blood samples were taken for CYP2D6 polymorphism analysis. Systemic inflammation was assessed based on laboratory and clinical indicators. All patients received 100 mg of tramadol intravenously every 6 h during the first postoperative day. Postoperative pain was assessed before and 30 min after tramadol injections. Tramadol, ODT, and NDT concentrations were determined by high-performance liquid chromatography. Results:CYP2D6 analysis revealed 2 poor (PM), 22 intermediate (IM), 22 extensive (EM), and 1 ultrafast metabolizer. After a dose of 100 mg of tramadol, t1/2 of 4.8 (3.2–7.6) h was observed. There were no differences in tramadol concentration among metabolic phenotypes. The area under the concentration–time curve at the first dose interval (AUC1-6) of tramadol was 1,200 (917.9–1944.4) μg ×h ×L−1. NDT concentrations in UM were below the limit of quantification until the second dose of tramadol was administrated, while PM had higher NDT concentrations compared to EM and IM. ODT concentrations were higher in EM, compared to IM and PM. ODT AUC1-6 was 229.6 (137.7–326.2) μg ×h ×L−1 and 95.5 (49.1–204.3) μg ×h ×L−1 in EM and IM, respectively (p = 0.004). Preoperative cholinesterase activity (ChE) of ≤4244 U L−1 was a cut-off value for a prediction of systemic inflammation in an early postoperative period. NDT AUC1-6 were significantly higher in patients with low ChE compared with normal ChE patients (p = 0.006). Pain measurements have confirmed that sufficient pain control was achieved in all patients after the second tramadol dose, except in the PM. Conclusions:CYP2D6 polymorphism is a major factor in O-demethylation, while systemic inflammation accompanied by low ChE has an important role in the N-demethylation of tramadol in postoperative patients. Concentrations of tramadol, ODT, and NDT are lower in surgical patients than previously reported in non-surgical patients. Clinical Trial Registration: ClinicalTrials.gov, NCT04004481.